Science activity-enhanced content-based instruction effects on grade two pupil achievement and attitude - Daplin, Maria Doreen S. Atillo (2008)
Two grade 2 classes in Kapitan Tomas Monteverde Sr. Central Elementary School, Davao City were the subjects of this study which aimed to determine the effects of Science Activity-Enhanced Content-Based Instruction (SAE CBI) on Science and English achievement and their attitude towards the subjects. The instruments used were the Science and English achievement tests and attitude rating scale. The achievement pretest results were insignificant. The Posttest results showed that the SAE CBI group was signficantly higher than that of the existing CBI group in Science and English achievement. However, both groups made significant positive improvement on their attitudes based on the pretest-posttest mean scores. Both approaches improved the pupils' attitude towards learning of the subject.